2014
DOI: 10.1007/s12035-014-8707-8
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Extracellular Signal-Regulated Kinase1/2 in the Medial Prefrontal Cortex Contributes to Stress-Induced Hyperalgesia

Abstract: Stressful stimuli can exacerbate persistent pain disorder. However, the underlying mechanism is still unknown. Here, to reveal the underlying mechanism for stressful stimuli-induced hyperalgesia in chronic pain, we investigated the effect of extracellular signal-regulated kinase1/2 (ERK1/2) activation on pain hypersensitivity using single-prolonged stress (SPS) model, complete Freund's adjuvant (CFA) model and SPS + CFA model. The experimental results revealed significantly reduced paw withdrawal threshold in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…PWT was further reduced in injured hindpaws of the SPS + CFA-exposed rats from day 9 after CFA injection compared to CFA-exposed rats (P < 0.05)7. In the present study, there was a significant effect (A, F 2,105  = 95.72, P < 0.001; B, F 3,140  = 84.33, P < 0.001) on the paw withdrawal thresholds (PWTs).…”
Section: Resultssupporting
confidence: 41%
See 3 more Smart Citations
“…PWT was further reduced in injured hindpaws of the SPS + CFA-exposed rats from day 9 after CFA injection compared to CFA-exposed rats (P < 0.05)7. In the present study, there was a significant effect (A, F 2,105  = 95.72, P < 0.001; B, F 3,140  = 84.33, P < 0.001) on the paw withdrawal thresholds (PWTs).…”
Section: Resultssupporting
confidence: 41%
“…Previous studies conducted by our research group have demonstrated that exposure to PTSD can enhance CFA-induced allodynia7. Both CFA- and SPS + CFA-treated animals demonstrated mechanical hyperalgesia compared to the control group.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Many studies have shown the positive correlation between preoperative anxiety and postoperative pain intensity as well as analgesic consumption [5][6][7][8][9]. The phenomenon that exposure to physical or psychological stressors can enhance nociception and pain sensitivity is described as stress-induced hyperalgesia (SIH) [10][11][12][13][14][15][16]. Although more and more attention has been paid to investigate this phenomenon, the potential underlying molecular mechanism has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%